1998
DOI: 10.1159/000030338
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Presentation of a Foreign Body in the Urinary Bladder: A Migrant Intrauterine Device

Abstract: A 35-year-old woman, who had had an intrauterine device inserted 7 years earlier, presented with dysuria, pollakiuria, suprapubic pain and urethral irritation. The intrauterine device was found in the bladder with stone formation and was removed by endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The human medical literature contains multiple case reports of intravesical foreign bodies (Göğüs et al, 2002; Junceda Avello et al, 1977; Mannan et al, 2011; Nishiyama et al, 2002; Rajaie Esfahani & Abdar, 2007; Woods & Wise Jr., 1980; Yalçin et al, 1998). Most of these are iatrogenically or self‐introduced into the bladder but perforation and migration from adjacent organs (Baumgartner et al, 1990; Mannan et al, 2011; Van Ophoven & DeKernion, 2000) have also been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human medical literature contains multiple case reports of intravesical foreign bodies (Göğüs et al, 2002; Junceda Avello et al, 1977; Mannan et al, 2011; Nishiyama et al, 2002; Rajaie Esfahani & Abdar, 2007; Woods & Wise Jr., 1980; Yalçin et al, 1998). Most of these are iatrogenically or self‐introduced into the bladder but perforation and migration from adjacent organs (Baumgartner et al, 1990; Mannan et al, 2011; Van Ophoven & DeKernion, 2000) have also been described.…”
Section: Discussionmentioning
confidence: 99%
“…The human medical literature contains multiple case reports of intravesical foreign bodies (Göğüs et al, 2002;Junceda Avello et al, 1977;Mannan et al, 2011;Nishiyama et al, 2002;Rajaie Esfahani & Abdar, 2007;Woods & Wise Jr., 1980;Yalçin et al, 1998).…”
Section: F I G U R E 2 Quick Release Tourniquet Used In Small Animal ...mentioning
confidence: 99%
“…These foreign bodies act as a nidus for stone formation in the bladder. Some reports in the literature showed that bladder stone formation was the result of complication following surgeries [10] .…”
Section: Discussionmentioning
confidence: 99%